(untitled) (Nusantara Medical Science Journal, 2025)
Introduction: Fibrinolytic therapy is preferred for ST-segment elevation myocardial infarction (STEMI) when the timeframe for percutaneous coronary intervention (PCI) cannot be achieved. Although effective, fibrinolytics are also associated with several adverse effects in addition to the complications of STEMI itself. Case: A 45-year-old active smoker man presented with chest pain, dyspnea, and diaphoresis for the past hour. Electrocardiography revealed infero-posterior STEMI with right ventricular infarction. Echocardiography demonstrated akinetic inferior, infero-septal, and posterior walls with an estimated right atrial pressure of 15 mmHg. Management: Therapy consisted of aspirin, clopidogrel, furosemide, and streptokinase infusion. Within five minutes of initiating streptokinase, the patient developed sudden hypotension that required norepinephrine, dobutamine, and dopamine. At approximately halfway of the streptokinase infusion, he developed accelerated idioventricular rhythm which progressed to pulseless ventricular tachycardia lasting for one minute. Before defibrillation was performed, his rhythm reverted to sinus, after which a bolus of amiodarone was administered. Given his instability, streptokinase was discontinued after approximately 70 percent of the total dose had been delivered. Outcome: The patient was transferred to the intensive care unit with stable hemodynamic, resolved chest pain, and more than 50 percent ST-segment resolution on ECG. Heparin, atorvastatin, maintenance amiodarone, and furosemide were added to his regimen. He continued to improve clinically and was discharged without complication. Conclusion: This case shows that fibrinolysis remains essential when PCI is unavailable, but streptokinase can cause hemodynamic and arrhythmic complications, highlighting the need for close monitoring and rapid intervention in resource-limited settings.